Peran Prostodonsia dalam Identifikasi Manusia: Aspek Terlupakan dalam Odontologi Forensik - Sarwono, Aditya P. (e-GiGi, 2024)
Abstract: Human identification continues to pose a significant challenge, with thousands of individuals or corpses remaining unidentified each year, as reported by the National Missing and Unidentified Person System (NamUs). Forensic odontology becomes exceptionally crucial when visual/facial identification and fingerprinting fail, such as in disasters or decomposed remains. By leveraging the expertise of dentists, forensic odontology makes a valuable contribution to the legal system. High-quality dental records are paramount for human identification. Forensic dentistry provides scientific data for legal proceedings. The robust structure of teeth and resilient restorative materials are pivotal in the identification process. Prosthodontics, especially for denture wearers, plays a significant role, with equipment like denture labeling gaining popularity. Specialization in prosthodontics is vital for understanding dental materials, labeling techniques, palatal rugae patterns, bite marks, and lip prints. Application of effective methods in forensic odontology is of paramount importance in identifying individuals. Remarkably, prosthetics in the field of forensic dentistry remains relatively unexplored and often overlooked, even in Indonesia, despite its significant potential in the realm of forensics. In conclusion, forensic identification using prosthodontic tools such as labeling or marking on dentures can provide crucial identification clues. Dental marking techniques namely surface modification techniques and inclusion techniques, have their respective advantages and disadvantages. Keyword:  human identification; forensic odontology; denture; identification methods   Abstrak: Identifikasi manusia tetap menjadi tantangan signifikan, dengan ribuan individu atau jenazah yang tidak teridentifikasi setiap tahunnya, seperti yang dilaporkan oleh National Missing and Unidentified Person System (NamUs). Odontologi forensik menjadi sangat penting ketika identifikasi visual/wajah dan sidik jari gagal, seperti pada bencana atau jenazah yang terurai. Dengan memanfaatkan keahlian dokter gigi, odontologi forensik memberikan kontribusi pada sistem hukum. Catatan gigi berkualitas tinggi sangat penting untuk identifikasi manusia. Odontologi forensik menyediakan data ilmiah untuk proses hukum. Struktur gigi yang kuat dan bahan restoratif yang tahan terhadap kerusakan menjadi kunci dalam identifikasi. Prostodonti, khususnya bagi pemakai gigi palsu, memainkan peran yang signifikan, dengan peralatan seperti label gigi palsu semakin populer. Spesialisasi dalam bidang prostodontik sangat penting dalam memahami bahan gigi, teknik penandaan, pola rugae palatal, bekas gigitan, dan bekas bibir. Menerapkan metode-metode yang efektif dalam odontologi forensik sangat penting untuk mengidentifikasi individu. Secara mencolok, prostetik dalam ranah odontologi forensik tetap relatif belum tersentuh, sering kali terabaikan di Indonesia meskipun memiliki potensi signifikan dalam dunia forensik. Simpulan studi ini ialah identifikasi forensik dengan menggunakan peralatan prostodontik seperti pelabelan atau pemberian tanda pada gigi tiruan dapat memberikan petunjuk identifikasi penting. Teknik penandaan gigi yaitu surface modification technique dan inclusion technique dengan keunggulan dan kekurangan masing-masing. Kata kunci: identifikasi manusia; odontologi forensik; gigi palsu; metode identifikasi